Strongman : the rise of five dictators and the fall of democracy - Davis, Kenneth C. (Square Fish, 2022)
Profiles the lives and political careers of five dictators in recent history including Benito Mussolini, Adolph Hitler, Mao Zedong, Joseph Stalin, and Saddam Hussein. Explores how they came to power, their effect on their home countries, and the lessons that can be learned from their authoritarian roles. Includes timelines, quotes, and black-and-white photographs.